Peningkatan Kompetensi Menuliskan Penjumlahan dan perkalian Bilangan Melalui Penggunaan Alat Peraga Kartu Bilangan Pada Siswa Kelas II SDN Sukolilo 250 Surabaya - Soebagio, Bambang Didik; Andharu, Devito (Jurnal Ilmiah FONEMA : Jurnal Edukasi Bahasa dan Sastra Indonesia, 2016)
The research objective of this clas action is to describe the increase in competencies write addition and multiplication of number through the use of props card number and the student’s attention when be joined the study consisted of four activities, namely the action, observation and tes methods. Data analysis technique used was qualitative descriptive with percentage calculation. The conclusions of this studi are: (1) enhancing the competence to write addition and multiplication grade II SDN Sukolilo 250 Surabaya can be done through the use of props card numbers; (2) the use of props card number can increase student attention whli following the ongoing learning